SAT0209 A SIMPLIFIED APPROACH FOR SLE PATIENTS TO REPORT DISEASE ACTIVITY USING A REVISED VERSION OF THE SWEDISH SYSTEMIC LUPUS ACTIVITY QUESTIONNAIRE. (June 2019) - Pettersson, Susanne; Illescas-Bäckelin, Vera; Jonsen, Andreas; Gunnarsson, Iva; Trysberg, Estelle; Leonard, Dag; Sjowall, Christopher; Svenungsson, Elisabet
Abstract : Background: The Systemic Lupus Activity Questionnaire (SLAQ) is a validated questionnaire, which captures patients' assessments of SLE-related symptoms and disease activity (1). However, it is extensive and in a recent study we found that some questions were difficult to answer, added little information, or had poor correlation with physicians' assessments (2). Thus, herein we revised the Swedish version of the questionnaire (SWE-SLAQr), building on previous results and we also asked patients for input. Our aim was to get an improved and shorter version, to support clinical work and online registries. The original SLAQ includes 26 items, while SWE-SLAQr includes 20 items. Objectives: We compared patients' assessments of SLE disease activity, as reported in the SWE-SLAQr, with physicians' assessments using SLE activity measure (SLAM) and SLE disease activity index (SLEDAI-2K). In addition, we evaluated the performance of the symptom items of SWE-SLAQr as compared to the corresponding items in SLAM. Methods: Patients filled out SWE-SLAQr prior to physicians' assessments. Correlations between SWE-SLAQr-total, sub-scales (Symptom score, Patients global) and SLAM-excluding the 7 laboratory items (SLAM-nolab), SLAM and SLEDAI-2K as well as between the corresponding items in SLAQ and SLAM, were evaluated using Spearman's ρ. Results: We included 101 patients, 85% women, median age 43 (IQR 22) years, disease duration 14 (IQR 15) years. Patients reported more symptoms than recorded by doctors. Correlations between patients' and physicians' assessments were for SLAM-nolab: SWE-SLAQr total, ρ=0.674, Symptom score, ρ=0.670, and Patients global, ρ=0.667, as expected the correlations were lower for SLAM: SWE-SLAQr total, ρ=0.472, Symptom score, ρ=0.467, and Patients global, ρ=0.501. No correlations were found between patients' and physicians' assessments when using SLEDAI-2K (ρ<0.09 for all). Of symptom items fatigue (ρ=0.741), alopecia (ρ=0.695) and weight loss (0.517) showed highest degree of correlation. Notably, symptoms of dyspnea/pleuritic chest pain had no correlation between patients' and physicians' assessments (ρ=0.152, p=0.130). Conclusion: We conclude that SWE-SLAQr performed equally well as SLAQ (2), demonstrating that it can be used to monitor disease activity. We encourage further use of SWE-SLAQr and recommend its implementation in clinical care, we believe it is especially well suited to support digital and telephone contacts. However further attention is needed to evaluate the discrepancy between physicians' and patients' evaluation of thoracic pain/symptoms. References: [1] Karlson EW, et al. Validation of a Systemic Lupus Activity Questionnaire (SLAQ) for population studies. Lupus. 2003. [2] Pettersson S, et al. A comparison of patients' and physicians' assessments of disease activity using the Swedish version of the Systemic Lupus Activity Questionnaire. Scand J Rheumatol. 2017. Disclosure of Interests: None declared